Dynamic responses of gut microbiota to agricultural and wildfire ash: insights from different amphibian developmental stages - Tong, Qing; Xu, Ming-da; Fan, Qiu-ru; Pan, Yue-liang; Long, Xin-zhou; Dong, Wen-jing; Cui, Li-yong; Luo, Zhi-wen (Frontiers in Microbiology, 2025)
Combustion by-products—specifically wildfire ash and rice-straw ash—are emerging contaminants in freshwater ecosystems. However, their impacts on amphibian survival and gut microbiota across various developmental stages remains largely unclear, thereby limiting evidence-based conservation strategies in fire-affected habitats. This study evaluated the effects of artificial water (control, C) and aqueous extracts of ash (AEAs) derived from wildfire ash (W) and rice straw ash (S) on the survival and gut (G) microbiota of Rana dybowskii tadpoles (T) and adult frogs (F). Exposure to wildfire ash significantly reduced tadpole survival compared to rice straw ash, whereas no significant differences were observed in adult frogs. Alpha diversity of the gut microbiota differed significantly among tadpole groups but not among adult groups. Bray-Curtis and weighted UniFrac analyses revealed significant differences in the gut microbiota of adult frogs and tadpoles across different treatment groups. Linear discriminant analysis effect size (LEfSe) identified a significant enrichment of specific bacterial genera across treatment groups. BugBase analysis indicated that in the TCG, TSG, and TWG groups, notable variations in the TCG, TSG, and TWG groups, there were notable differences in Forms-Biofilms and Potentially-Pathogenic, while in the FCG, FSG, and FWG groups, significant differences were observed in Aerobic, Gram-Positive, Potentially-Pathogenic, and Stress-Tolerant. These findings suggest that wildfire ash exhibits greater toxicity than rice straw ash to both life stages of R. dybowskii, with tadpoles being more vulnerable. By elucidating the link between ash-derived pollutants and amphibian gut health, this study underscores the growing threat of routine straw burning and intensifying wildfires to global freshwater biodiversity and advocates for ash-specific mitigation measures and microbiota-informed conservation strategies.